2006
DOI: 10.1385/bter:113:3:273
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Trichophytosis on Serum Zinc Levels in Calves

Abstract: The purpose of this study was to determine the zinc levels in calves with trichophytosis and to research the importance of zinc for fungi. The sera of 20 calves with trichophytosis and 10 healthy calves were used in this study. Zinc levels of the sera were measured by the atomic absorption spectrophotometer method. Serum zinc levels of diseased and healthy animals were found to be 42.0+/-16.6 microg/dL and 75.8+/-5.9 microg/dL, respectively. Serum zinc levels of diseased calves were lower than healthy ones and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
4
8
0
Order By: Relevance
“…A positive correlation between SOD and Zn and between SOD and Cu is reported (r=0.55, r=0.58 and r=0.73, r=0.68 in both healthy and affected animals, respectively). The decreasing activity of the erythrocyte GSHPx and SOD in dermatophytic calves may be related to the consumption of the cofactors Se, Cu, and Zn by dermatophytes; these results agree with previous work [5,22]. Pasa and Kiral [27] have reported a significant decline in serum Zn and vitamin A in calves with dermatophytosis.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…A positive correlation between SOD and Zn and between SOD and Cu is reported (r=0.55, r=0.58 and r=0.73, r=0.68 in both healthy and affected animals, respectively). The decreasing activity of the erythrocyte GSHPx and SOD in dermatophytic calves may be related to the consumption of the cofactors Se, Cu, and Zn by dermatophytes; these results agree with previous work [5,22]. Pasa and Kiral [27] have reported a significant decline in serum Zn and vitamin A in calves with dermatophytosis.…”
Section: Discussionsupporting
confidence: 91%
“…Serum Zn concentration in affected calves with dermatophytosis is significantly (P≤0.05) lower than that in healthy control calves (0.86±0.09 ppm). This is in agreement with [5,21]. The abnormalities of trace elements could be a result of primary dietary imbalances or a result of other secondary The values represent the mean ± SD diseases.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…No significant alteration was seen in total red blood cells, the blood indices (MCV, MCH and MCHC) and the packed cell volume in the infected goats this result is in agreement with Anindita D, et al and disagreement with Nisbet C, et al who found significantly low PCV [16,17]. None of the infected goats showed anaemia so no significant difference was observed in haemoglobin our findings in agreement with Anindita D, et al Karapehlivan M, et al although it is disagreed with Nisbet C, et al who reported that infected sheep with T.mentagrophytes had anaemia due to significantly low haemoglobin Significant reduction of white blood cells in the infected goats this result is in agreement with Anindita D, et al who reported significant reduction in total erythrocyte count, total leukocyte count and the percentage of neutrophils in calves with dermatophytosis, also Nisbet C, et al found significant reduction in total erythrocyte count while Karapehlivan M, et al reported no significant alteration in total erythrocyte count [16][17][18].…”
Section: Discussionsupporting
confidence: 86%